Pengelolaan Sumber Daya pada UMKM ADK Terbang Menggunakan Metode American Productivity Center untuk Meningkatkan Produktivitas dan Profitabilitas - Hakim, Lukman; Mas'ud, M. Imron (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2024)
Productivity is the key for business actors to compete in a highly competitive market. Productivity is closely related to the effectiveness and efficiency of using resources in producing output. This research focuses on Flying ADK MSMEs, which shows a significant increase in production in three periods (May 2023 – March 2024). Production achievement that continues to approach the set targets shows great potential for growth, but requires further strategic interventions to improve efficiency and competitiveness. The purpose of the study is to analyze the level of productivity, profitability, and price improvement factors in ADK Fly MSMEs and provide recommendations for improvement. The method used is the American Productivity Center (APC), to measure productivity, profitability, and price improvement factors through optimizing the use of resources such as labor, raw materials, energy, and capital. The measurement results showed an increase in productivity of 1.4% in the second period and 0.4% in the third period. Profitability also increased by 1.4% and 0.4% in the same period. The price improvement index increased every year, reaching 0.97% in the second period and 0.93% in the third period, which had a positive impact on the company's productivity and profitability. This increase was analyzed in detail using a fishbone diagram. The results of this study provide recommendations that can be used by business actors to optimize resources and improve operational efficiency.